Sous-Vide as a technique for preparing healthy and high-quality vegetable and seafood products - Zavadlav, Sandra (2020)
Sous-vide is a technique of cooking foods in vacuum bags under strictly controlled temperature, offering improved taste, texture and nutritional values along with extended shelf life as compared to the traditional cooking methods. In addition to other constituents, vegetables and seafood represent important sources of phytochemicals. Thus, by applying sous-vide technology, preservation of such foods can be prolonged with almost full retention of native quality. In this way, sous-vide processing meets customers' growing demand for the production of safer and healthier foods. Considering the industrial points of view, sous-vide technology has proven to be an adequate substitute for traditional cooking methods. Therefore, its application in various aspects of food production has been increasingly researched. Although sous-vide cooking of meats and vegetables is well explored, the challenges remain with seafoods due to the large differences in structure and quality of marine organisms. Cephalopods (e.g., squid, octopus, etc.) are of particular interest, as the changes of their muscular physical structure during processing have to be carefully considered. Based on all the above, this study summarizes the literature review on the recent sous-vide application on vegetable and seafood products in view of production of high-quality and safe foodstuffs.